Correlation between Accessibility of Health Facilities and Drug Side Effects with Elderly Non-Adherence in Undergoing Tuberculosis Treatment at the Tanjung Selor Health Center - Joko Sapto Pramono; Riana Sudding; Tini (PT FORMOSA CENDEKIA GLOBAL, 2023)
The aging process causes decreased function of various body systems that are vulnerable to the side effects of anti-tuberculosis drugs. The accessibility of health facilities is also a determinant of the success of the treatment of tuberculosis patients. The purpose of this study was to analyze the relationship between drug side effects and accessibility of health facilities with non-adherence to treatment in elderly patients at the Tanjung Selor Health Center. This type of research was descriptive analytic with a cross-sectional approach. Samples were taken from all tuberculosis elderly who were being treated for as many as 30 respondents. The results of the chi square analysis of the relationship between accessibility of health services and non-compliance obtained p-value = 0.026, and drug side effects with non-adherence p-value= 0.016, (<α=0.005). The authors conclude that there is a significant relationship between the accessibility of health facilities and drug side effects with non-adherence of the elderly in the treatment of tuberculosis.